Comparison of Olfactory Function Before and After Endoscopic Sinus Surgery in Patients of Chronic Rhinosinositis with Sinonasal Polyps - Elahi, Sh. Sarmad; Bajwa, Faiza; Ilyas, Muhammad; Khan, Hurtamina; Niaz, Adeel; Hussain, Sobia (Indus Journal of Bioscience Research, 2025)
Background: Chronic rhinosinusitis with sinonasal polyps (CRSwNP) is a prevalent condition associated with olfactory dysfunction, nasal obstruction, and facial pain. Endoscopic sinus surgery (ESS) is a common treatment option for patients with CRSwNP, but the effect of ESS on olfactory function remains under debate. Objective: This study aims to evaluate the changes in olfactory function before and after ESS in patients with CRSwNP and sinonasal polyps. Methods: This Descriptive case series was conducted in the department of ENT, Lahore General Hospital, Lahore, from September 2024 to January 2025. Data were collected through the Non-probability consecutive sampling technique. The participant was admitted to the ENT ward for surgery. Functional endoscopic sinus surgery was performed under GA in each case with the standard anterior-to-posterior approach. Post-operative follow-up was carried out at the 3rd month. Results: A total of 69 patients were added in the study and the mean age was 45.2 ± 9.3 years, with 52% males and 48% females. The duration of symptoms ranged from 12.5 ± 6.4 months on average, with no significant gender differences. 25% of the patients were smokers, and 40% had a history of allergies. All patients included in the study had a preoperative olfactory score of 0, indicating complete anosmia before undergoing functional endoscopic sinus surgery (FESS). At the three-month follow-up, 68.1% of patients demonstrated improvement in olfactory function, scoring 1 on the olfactory test, indicating the ability to identify phenyl ethyl alcohol (50%). However, 31.9% of patients remained anosmic, unable to distinguish between the odorless substance and the test solution. Conclusion: ESS significantly improves olfactory function and alleviates other sinonasal symptoms in patients with CRSwNP. The degree of polyp removal correlates with olfactory recovery, and ESS enhances overall quality of life.